2019
DOI: 10.1080/19476337.2018.1554703
|View full text |Cite
|
Sign up to set email alerts
|

Physical–chemical characterization and antioxidant properties of extruded products made from mixtures composed of corn grits and red potato flour (Oxalis tuberosa)

Abstract: Lira (2019) Physical-chemical characterization and antioxidant properties of extruded products made from mixtures composed of corn grits and red potato flour (Oxalistuberosa),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In recent years, the research areas to develop the ready to eat food or snacks with higher antioxidant activity have been increased [1] , [2] , [3] , [4] . Antioxidant rich foods have potential role in prevention or delaying atherosclerosis, heart disease, cerebrovascular, stroke, diabetes mellitus rheumatoid arthritis, osteoporosis, ulcers, sunburn, cataracts, and aging [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the research areas to develop the ready to eat food or snacks with higher antioxidant activity have been increased [1] , [2] , [3] , [4] . Antioxidant rich foods have potential role in prevention or delaying atherosclerosis, heart disease, cerebrovascular, stroke, diabetes mellitus rheumatoid arthritis, osteoporosis, ulcers, sunburn, cataracts, and aging [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, snacks enriched with Jerusalem artichoke and pumpkin showed similar WSI values, lower values than those of the controls, and amaranth snacks (Pęksa et al, 2016). González Victoriano et al (2019) did not find significant differences with respect to the control in WAI and observed that it is inversely proportional to the concentration of red potato flour; in terms of the WSI, all the treatments presented differences with respect to the control, and the extrudates made with flour of red potatoes presented the highest value. Castro‐Mendoza et al (2019) explained that the highest WAI values were observed in the samples with the highest concentration of oca.…”
Section: Effect Of Use Of Tubers On the Physicochemical And Technofun...mentioning
confidence: 91%
“…In another article, the increase in carrot caused the decrease in EI, also the increase in temperature and moisture favored the expansion (Upadhyay et al, 2010). Singh et al (2016) obtained that there was a reduction in the EI of the extrudates with the incorporation of beet; however, the temperature did not show a significant effect, otherwise with González Victoriano et al (2019) & Rodríguez‐Miranda et al (2011) who observed a higher EI in extrudates made with red potato flour and taro flour respectively, compared to the control. Pensamiento‐Niño et al (2018) and Peluola‐Adeyemi and Idowu (2014) reported that the increase in moisture decreased the EI and the increase in temperature favored the expansion of snacks with taro.…”
Section: Effect Of Use Of Tubers On the Physicochemical And Technofun...mentioning
confidence: 92%